A satellite study of the tropical easterly jet stream during ‘Monsoon-77’ (MAUSAM, 1982)
This is an observational study of the tropical easterly jet in the cloud field. The visible and infrared imagery of NOAA-5, US weather satellite, have been used to study jet stream  clouds in conjunction with the available upper air radiowind observations over India and neighbourhood during Monsoon-77 (20-26 June). The jet-stream clouds have been observed in association with perturbations in upper tropospheric easterly currents. The observed cloud patterns are found to agree fairly well with the corresponding maximum wind field and sometimes with the motion fields of 150 and 100 mb. The organisation of clouds in longitudinal and transverse modes having dependence on verticle wind shear have also been observed. The values of vertical wind shear computed in cases of the satellite-viewed jet-stream clouds are found to vary from 25 to 32 hr-l about 5 km below the jet core, which are more than the values reported by earlier workers based on the study of the jet in the wind field. Monsoon is observed to be active in the right entrance sector of the jet clouds and the convective activity appears to be more pronounced when a surface low pressure system is present over the area.